2004
DOI: 10.1111/j.1369-7625.2004.00271.x
|View full text |Cite
|
Sign up to set email alerts
|

Patient‐focussed decision‐making in early‐stage prostate cancer: insights from a cognitively based decision aid

Abstract: Purpose To study the cognitive processes of early-stage prostate cancer patients as they determined which treatment they preferred, using our cognitively based decision aid.Method The aid was a one-to-one interview that included the structured presentation of information, listing exercises in which the patient identified attributes important to his decision, and trade-off exercises to help him weigh and integrate those attributes together. At various points of the interview, patients identified the attributes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
69
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 76 publications
(71 citation statements)
references
References 33 publications
2
69
0
Order By: Relevance
“…It is also possible that men rapidly differentiate and consolidate options to manage decisions, as espoused by decision-making theory [34,36]. The findings also indicate that some men defer treatment decisions to their doctors [16,22].…”
Section: Discussionmentioning
confidence: 87%
“…It is also possible that men rapidly differentiate and consolidate options to manage decisions, as espoused by decision-making theory [34,36]. The findings also indicate that some men defer treatment decisions to their doctors [16,22].…”
Section: Discussionmentioning
confidence: 87%
“…When patients were asked to rank all the factors that were important to their decision, urinary function and bowel function were the only 2 factors found to be important to greater than 50% of patients. 26 This study also found that fewer than 20% of men reported sexual functioning as 1 of the top 3 attributes important to their decision, although 32% mentioned that it was important. A different study found that 49% of men were concerned about incontinence and 38% were concerned about impotence.…”
Section: Treatment-related Side Effects and Their Impact On Healthrelmentioning
confidence: 86%
“…For example, in 1 study of 60 patients, 18 different attributes of treatment were identified as being the "most important." 26 …”
Section: -71mentioning
confidence: 99%
See 2 more Smart Citations